Immunotherapy of colon cancer - Kowalczyk, Dariusz W. (Contemporary Oncology/Współczesna Onkologia, 2006)
Despite many difficulties, immunotherapy of colon cancer becomes more effective and slowly enters into everyday clinical practice. The long way from unspecific immune stimulators such as levamisole, BCG, interleukins and interferons ended up in specific anti-cancer vaccines and precise antibody based therapeutics. Nowadays, among novel anticancer agents used in colon cancer therapy there is a place for vaccines such as OncoVax and monoclonals including cetuximab, bevacizumab and panitumumab.